Schottky emission in nanoscopically crystallized Ce-doped SnO2 thin films deposited by sol-gel-dip-coating - Pinheiro, Marco A. L. [UNESP]; Pineiz, Tatiane F. [UNESP]; de Morais, Evandro A. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Saeki, Margarida Juri [UNESP]; Cavalheiro, Alberto A. (Elsevier B.V. Sa, 2008)
This paper reports the electrical effects of the incorporation of Ce(III) or Ce(IV) in SnO2 thin films, prepared by the sol-gel-dip-coating technique. This doping has drastically increased the resistivity compared to undoped thin films. Nanoscopic dimension of crystallites, in the range 5-10 nm, contributes to this increase. The high number of crystallites decreases the mobility due to the increase of the density of potential barrier between grains per unit of volume. High doping leads to low conductivity when Ce(III) salt is used as precursor, which assures the acceptor-like nature of this ion in the matrix. Current as function of voltage, measured for several temperatures, leads to the predominance of Schottky conduction mechanism, even though a tunneling process seems to be a good approximation for the observed deviations at lower applied electric fields. The potential barrier for Schottky emission is in the range 0.6-0.8 eV. For Ce(IV) doping, an increase of the grain boundary depletion layer seems to be responsible for the observed high resistivity, because it leads to higher electron scattering at grain boundary. Measurements done under room atmosphere lead to a higher barrier height than measurement done under vacuum conditions, due to oxygen adsorption at particles surface. For temperatures higher than 150 degrees C, under vacuum conditions, the elimination of O-2(-) species becomes probable, increasing considerably the current density. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Tin oxide; Cerium; Electrical properties; Measurements